Comparative Analysis of Atherosclerosis Risk Factors in the Staff of the Tbilisi (Georgia) Cleaning Service - Kantaria Murman; Machavariani Pavle; Ormotsadze Giorgi; Kakabadze Ketevan; Chkhikvishvili Irakli; Buleishvili Maka; Kipiani Nina; Agladze Vazha; Sanikidze Tamar (Journal of Antioxidant Activity, 2020)
Objective Search of pathogenetic mechanisms and risk factors of atherosclerosis in the employees of the cleaning service in Tbilisi. Materials and Methods As a result of a preliminary survey and examination of 200 employes of Tbilisi cleaning service aged 25-45 years (2014-2016), 22 patients with angina, hypercholesterolemia, intimae-media thickness > 0.65 mm, were selected into I group, and 23 individuals without these disorders into II group. In the blood plasma of the selected patients the intensity of oxidative metabolism parameters, TAA and MDA were determined. The variance and correlation analysis (АNOVA) was used for conducting the comparative analysis of the levels of studied parameters. Results In the combined group (I+II) there are several reliable correlations between the Age -TCol, Age-MDA, BMI-Tg, BMI-MDA, LDLChol-HDLChol, LDLChol–TChol, HDLChol-TChol, LDLChol-MDA, LDLChol-TAA. no correlation between these parameters in individual groups (I and II) was found. That indicates that we have an imaginary correlation related to the large intergroup difference between the average values of the group indicators, that is the values of various indicators change during the development of the pathological process, but there is no causal relationship between these alterations. The reliable TAA-MDA correlation in the combined group (I+II) is related to the high anticorrelation between these parameters and the significantly higher average value of TAA in the low-risk group (II) in comparison to the high-risk group (I). Conclusion The results analysis indicates both the diagnostic value of redox status indicators and their leading role in the atherogenesis processes. In populations with a high risk of atherosclerosis, monitoring of serum TAA is recommended.
Keywords: Risk-factors of atherosclerosis